A Bibliometric Analysis and Future Research Directions on Language and Literacy - Hazlina, Abdullah; Syadiyah, Abdul Shukor; Humaira, Raslie; Ezihaslinda, Ngah; Noryani Neni, Ahmad Jamain (Human Resource Management Academic Research Society (HRMARS), 2023)
There has been considerable research conducted in the area of language and literacy focussing on themes such as reasons and factors, performance and achievements, ways, and methods for improvement, as well as risks and problems. However, an overview of a worldwide depiction of the research conducted in this area is hard to find. Thus, this research aimed to ascertain the global developments and trends in language and literacy over time by analysing three main levels of analysis: sources, authors, and documents. A bibliometric analysis was utilised to examine a final sample of 1,463 articles published in approximately the last 22 years (2000-2023). In carrying out the analysis, the bibliometrix R-Tool was used and the metadata from the SCOPUS database was retrieved. The results demonstrated an upward trend of publications with a high number of single-country publications and a fair number of multiple-country publications. The primary conclusion reveals that language and literacy can be considered a substantial field of research, and the most important themes identified are connected to five thematic clusters: (1) General development in language and literacy (2) Language and literacy in Early Childhood Education (ECE) (3) Language and literacy in English as a Second Language (ESL), (4) Issues in language and literacy and (5) Language and literacy for bilinguals. The field is also marked by constant growth; as indicated by the international collaborations, new trends and other related fields that conveyed great interest in the areas of language and literacy. These findings are crucial in informing researchers, educators and policy makers on the current needs related to language and literacy implementations, as well as potential research endeavours that are critical to the development of the field.